Emerging dynamics in audiences' consumption of trans-media products : the cases of Mad Men and Game of Thrones as a comparative study between Italy and New Zealand /: the cases of Mad Men and Game of Thrones as a comparative study between Italy and New Zealand. (2020) - Spano, Carmen
No abstract available